Predictive value of the Bayley Scales applied to a group of preterm infants, on their results in the Wechsler Scales at 10 years old - García-Martínez, María de la Paz; Sánchez-Caravaca, Juan; Montealegre-Ramón, María del Pilar; Pérez-López, Julio (Anales de Psicología / Annals of Psychology, 2018)
Objective.- The present work aims to verify if the scores obtained by a group of preterm infants during the first 3 years of life, evaluated with the Bayley scales, predict the posterior cognitive abilities, evaluated with the Wechsler Scales. Method.- A quasi-experimental method of descriptive type with a longitudinal design was used. To examine the predictive capacity of the assessments made with the BSID-II Scale on the results of the WISC-IV Scale, three canonical correlation analyzes were carried out, one initial, with the first month of corrected age data, another, with the 18 months corrected age and, third, at 36 months of chronological age. Results.- The scores obtained in the BSID-II Scales both at 18 months of corrected age and at 36 months of chronological age have a significant relationship with the results obtained at 9-11 years old on the WISC-IV Scale. However, the scores obtained at the corrected age month do not serve to predict such results. Conclusions.- These results allow us to highlight the predictive value of developmental evaluations performed after 18 months of corrected age, with good stability in cognitive development over time. We defend intervention and long-term follow-ups.